Fenomena Tikrār Dalam Al-Qur’an: Analisis Stilistika Pada Surah Al-Mursalat Dengan Pendekatan Tematik - Muhammad Haikal; Misnawati Misnawati; Hanif Dahlan (BASHA'IR: JURNAL STUDI AL-QUR'AN DAN TAFSIR, 2025)
This study explores the aesthetic and rhetorical dimensions of the Qur’anic discourse through an in-depth stylistic analysis of the repetitive phrase “waylun yauma’iżin lil-mukażżibīn” in Surah Al-Mursalat. Employing a qualitative descriptive method and a linguistic-stylistic tafsīr approach, the research draws upon six stylistic frameworks, repetition (tikrār), structural placement, phonostylistics, semantic variation, sound patterning, and rhetorical function. The findings reveal that the recurrence of this verse transcends mere rhetorical ornamentation; it serves as a theological and emotional reinforcement of divine warnings directed toward those who reject the truth. Each repetition emerges within distinct contextual frames, yet collectively constructs a cohesive structure of moral and spiritual resonance. Moreover, the rhythmic articulation of the verse enhances both its phonetic harmony and aesthetic power, illustrating the Qur’an’s capacity to intertwine linguistic artistry with spiritual depth. Conclusively, this research demonstrates that the Qur’anic language embodies an integrated system of meaning and beauty, where style becomes substance, and underscores the need for more advanced stylistic inquiry into the linguistic and spiritual dimensions of the Qur’an.